2016
DOI: 10.1007/164_2016_9
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and Histamine Receptors in Allergic Dermatitis

Abstract: In this chapter we will first introduce the pathophysiological process of several skin diseases including allergic dermatitis, a common skin disease, including chronic allergic contact dermatitis (CACD), and atopic dermatitis (AD). In CACD and AD patients, repeated skin exposure to antigens contributes to the development of chronic eczematous lesions. Repeated application of haptens on mice allows emulation of the development of CACD in humans. Further, we will focus on H1, H2, and H4 histamine receptors and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
0
24
0
2
Order By: Relevance
“…Although histamine is commonly associated with skin inflammation processes, for example, allergic dermatitis [ 60 ], it may play a regulatory role in other clinical conditions such as psoriasis, which is a multifactorial Th1/Th17-driven inflammation of the skin [ 61 ]. In a murine psoriasis-like model induced by imiquimod administration, Kim et al showed that the H4R agonist 4-methylhistamine ameliorated the clinical scores of psoriatic mice due to repression of Th1 cytokines and simultaneous induction of Treg cells [ 62 ].…”
Section: Regulatory and Immunomodulatory Functions Of Histaminementioning
confidence: 99%
“…Although histamine is commonly associated with skin inflammation processes, for example, allergic dermatitis [ 60 ], it may play a regulatory role in other clinical conditions such as psoriasis, which is a multifactorial Th1/Th17-driven inflammation of the skin [ 61 ]. In a murine psoriasis-like model induced by imiquimod administration, Kim et al showed that the H4R agonist 4-methylhistamine ameliorated the clinical scores of psoriatic mice due to repression of Th1 cytokines and simultaneous induction of Treg cells [ 62 ].…”
Section: Regulatory and Immunomodulatory Functions Of Histaminementioning
confidence: 99%
“…Histamine is a ubiquitous messenger molecule with multiple physiological activities that released from neurons, mast cells, and enterochromaffin-like cells [1]. It exerts various biological effects through its four cognate G proteincoupled histamine receptors: H1, H2, H3, and H4 (H1HR, H2HR, H3HR, and H4HR, respectively) [2]. Previous studies have shown that H1 histamine receptor (H1HR) is extensively involved in a wide array of pathological processes of allergy, such as atopic dermatitis, allergic rhinitis, and asthma [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a chronic inflammation of the airways that is often accompanied by extensive and variable airflow obstruction [1]. Allergic dermatitis is an inflammatory reaction that occurs at a contact site or part of the skin or mucous membrane after a single or multiple exposures to an exogenous substance [2]. Allergic rhinitis is characterized by at least two nasal symptoms: rhinorrhoea, blockage, sneezing or itching [3].…”
Section: Introductionmentioning
confidence: 99%